Studi Buyback Saham BUMN Di BEI Pada Masa Pandemi Covid 19 - Lindananty; Mohamad Soedarman (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
Abstract Stock buyback during the Covid 19 pandemic in 2020 which is intended to encourage the economy and increase stock prices that have decreased. To prove that these expectations are achieved or not, this study examines the differences in abnormal returns (AR) of stocks and trading volume activity (TVA) before and after share buybacks with a sample of 7 BUMN issuers who have realized share buybacks until the end of June 2020. Paired sample test results The t test shows that the p value of the AR variable is 0.042, which is smaller than = 0.05. Likewise, the p value of the TVA variable is 0.002 <0.05, which means that there is a difference between AR and TVA before and after the buyback of the shares of the 7 BUMN companies.